Aplikasi Response Surface Methodology pada Optimasi Penambahan Blast Furnace Slag Terhadap Waktu Pengikatan dan Kuat Tekan Semen - Hardjono Hardjono; Cucuk Evi Lusiani; Agung Ari Wibowo; Mochammad Agung Indra Iswara (Jurnal Teknik Kimia dan Lingkungan, 2020)
The production of clinker consumes high energy and causes high production cost of cement industry. It can be reduced by adding blast furnace slag as a mixture in cement production. The blast furnace slag - clinker mixture can produce cement with setting time and compressive strength according to SNI. The effect of the addition of blast furnace slag as a clinker mixture to the setting time and compressive strength of cement can be optimized by response surface methodology (RSM) using Central Composite Design (CCD). Optimization by using RSM aims to determine the optimum condition of the blast furnace slag – clinker mixture to the initial setting time, final setting time, and compressive strength. ANOVA test results and response surface analysis show that the addition of blast furnace slag into the cement mixture has a significant influence on the initial setting time, final setting time, and compressive strength. The addition of 5% blast furnace slag with 92.5% clinker in the mixture of clinker and gypsum is the optimum condition which gives a significant effect on the response variable.